Effects of a single dose of psilocybin on behaviour, brain 5-HT2A receptor occupancy and gene expression in the pig - Donovan, Lene Lundgaard; Johansen, Jens Vilstrup; Ros, Nídia Fernandez; Jaberi, Elham; Linnet, Kristian; Johansen, Sys Stybe; Ozenne, Brice; Issazadeh-Navikas, Shohreh; Hansen, Hanne Demant; Knudsen, Gitte Moos (European neuropsychopharmacology, 2021)
•Pigs respond to 0.08 mg/kg psilocybin i.v. with headshakes, scratching and rubbing behaviour.•A similar dose produce a cerebral 5-HT2A receptor occupancy of ~67%.•1 week after psilocybin exposure an immunology-related genetic response was seen in prefrontal cortex. Psilocybin has in some studies shown promise as treatment of major depressive disorder and psilocybin therapy was in 2019 twice designated as breakthrough therapy by the U.S. Food and Drug Administration (FDA). A very particular feature is that ingestion of just a single dose of psilocybin is associated with lasting changes in personality and mood. The underlying molecular mechanism behind its effect is, however, unknown. In a translational pig model, we here present the effects of a single dose of psilocybin on pig behaviour, receptor occupancy and gene expression in the brain. An acute i.v. injection of 0.08 mg/kg psilocybin to awake female pigs induced characteristic behavioural changes in terms of headshakes, scratching and rubbing, lasting around 20 min. A similar dose was associated with a cerebral 5-HT2A receptor occupancy of 67%, as determined by positron emission tomography, and plasma psilocin levels were comparable to what in humans is associated with an intense psychedelic experience. We found that 19 genes were differentially expressed in prefrontal cortex one day after psilocybin injection, and 3 genes after 1 week. Gene Set Enrichment Analysis demonstrated that multiple immunological pathways were regulated 1 week after psilocybin exposure. This provides a framework for future investigations of the lasting molecular mechanisms induced by a single dose of psilocybin. In the light of an ongoing debate as to whether psilocybin is a safe treatment for depression and other mental illnesses, it is reassuring that our data suggest that any effects on gene expression are very modest.